Consumo de alcohol y su incidencia en la conducta de un adulto joven de la Parroquia San Carlos del cantón Quevedo Provincia de Los Ríos - Moran Rodriguez, Maria Fernanda (2023)
In the present investigative work it was concluded that the incidence of alcohol consumption in the behavior of the young adult, from the San Carlos parish of the Quevedo canton, in which techniques and instruments were implemented that allowed the acquisition of truthful information; Therefore, the application of the tools that were used, for example, the identification test of disorders due to alcohol consumption (AUDIT), the Hamilton Depression Rating Scale (HDRS) plus what was mentioned in the speech by the patient, was detailed and it was achieved. Reach a presumptive diagnosis according to the criteria of the DSM5 and ICD-10. During the course of alcohol consumption, the affectation of the young man's behavior was evidenced, which led him to manifest signs and symptoms of depressive characteristics and high-risk alcohol consumption, according to the ICD-10 code, an F32. 1 with a diagnosis of moderate depressive episode and according to the DSM-5 coding, a F10.20 moderate alcoholism, for this reason it is proposed to develop a therapeutic scheme of Cognitive Behavioral Therapy (CBT), as a possible solution to the case study.